The chlorine isotope composition of Martian meteorites 2. Implications for the early solar system and the formation of Mars. (22nd January 2016) - Sharp, Zachary; Williams, Jeffrey; Shearer, Charles; Agee, Carl; McKeegan, Kevin
Abstract: We determined the chlorine isotope composition of 16 Martian meteorites using gas source mass spectrometry on bulk samples and in situ secondary ion microprobe analysis on apatite grains. Measured δ 37 Cl values range from −3.8 to +8.6‰. The olivine‐phyric shergottites are the isotopically lightest samples, with δ 37 Cl mostly ranging from −4 to −2‰. Samples with evidence for a crustal component have positive δ 37 Cl values, with an extreme value of 8.6‰. Most of the basaltic shergottites have intermediate δ 37 Cl values of −1 to 0‰, except for Shergotty, which is similar to the olivine‐phyric shergottites. We interpret these data as due to mixing of a two‐component system. The first component is the mantle value of −4 to −3‰. This most likely represents the original bulk Martian Cl isotope value. The other endmember is a 37 Cl‐enriched crustal component. We speculate that preferential loss of 35 Cl to space has resulted in a high δ 37 Cl value for the Martian surface, similar to what is seen in other volatile systems. The basaltic shergottites are a mixture of the other two endmembers. The low δ 37 Cl value of primitive Mars is different from Earth and most chondrites, both of which are close to 0‰. We are not aware of any parent‐body process that could lower the δ 37 Cl value of the Martian mantle to −4 to −3‰. Instead, we propose that this low δ 37 Cl value represents the primordial bulk composition of Mars inherited during accretion. The higher δ 37 Cl values seen in many chondrites are explained by later incorporation of 37 Cl‐enriched HCl‐hydrate.